Stimulasi Kreativitas Gerak Anak Melalui Senam Si Buyung - Eva Eriani; Dimyati Dimyati (STAI Auliaurrasyidin Tembilahan, 2020)
In general, gymnastics is only imitation of movement from beginning to end but in this study gymnastics is combined with stories that are imagined by children, which are then realized into motion with the aim of stimulating the creativity of early childhood movements. In this research si buyung’s gymnastic modified to be warming up, creative movements, and cooling down. The research was quantitative quasi-experimental method with one group time-series design on 52 children aged 4-5 years in Yogyakarta. Data collection used interviews and observations, then analyzed with Kruskal Wallis. The results showed that implemented si buyung’s gymnastic effectively to increase the movement creativity of children aged 4-5 years is evidenced by the acquisition of asymp.sig p-value. 0,000 <0.05 which means there is a significant difference in the average ranking of children's creativity in each treatment.